ANALISIS PERAN PEMERINTAH DAN MASYARAKAT DALAM SEKTOR EKONOMI MELALUI FINALISASI KEBIJAKAN - Novita, Yeyen; Wafiratulaela, Wafiratulaela; Wicaksono, Pandu Nur; Mustofa, Muammar Taufiqi Lutfi; Sari, Wann Nurdiana; Inawati, Yuni (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
One of the processes carried out by the government and the community to manage existing resources through collaboration between the government and the private sector is one of the meanings of economic development. This is done in the context of creating job opportunities as well as efforts to encourage economic growth in a region. Thus, it is important for the government and the community to play a role in solving macroeconomic problems. The final objective of this research is to analyze in depth the concept of the three-sector economy, the rationality of the role of government and society, the scope of the government's role, government policy instruments and an overview of al-hisbah. This study uses a literature study where information is obtained through a collection of books, a collection of scientific works, several theses, encyclopedias, a little information from the internet and even other sources. Research shows that in the economy three sectors are played by 3 roles including households, companies and the government. The rationality of the government's role is based on the consequences of collective obligations, and the failure of the market to realize falah. The analysis of the government's role includes: the role of allocation, distribution, stabilization, the role of the state in overcoming externalities and the role of the state related to the implementation of Islamic morality. There are also three policies that cover, among others: fiscal policy, monetary policy, and supply-side policy. Some basic thinking about the role of society consists of the consequences of fardhu kifayah, the existence of public property rights and the failure of the market and government. While hisbah is an institution controlled by the government through individual efforts specifically assigned to solve problems related to the moral, religious and economic fields.